2014
DOI: 10.5539/jsd.v7n4p95
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Minimum Tillage and Crop Rotation as Climate Change Adaptation Strategies on Farmer Welfare in Smallholder Farming Systems of Zambia

Abstract: Worldwide, climate change is currently recognized as one of the major challenges to increased food production. The agriculture sector is the main source of livelihoods, growth and foreign exchange earnings in many developing countries including Zambia. However, it is also a sector that is mostly vulnerable to effects of climate change. Smallholder farmers in Zambia have been adopting agricultural related adaptation strategies including minimum tillage and crop rotation to mitigate effects of climate change. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…For example, Kasanga and Daka (2013) suggest 41% MT adoption in the 16 districts. Kuntashula, Chabala, and Mulenga (2014) and , respectively, found 12% and 13% adoption in their study areas in agro ecological zones 1 and 2a.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Kasanga and Daka (2013) suggest 41% MT adoption in the 16 districts. Kuntashula, Chabala, and Mulenga (2014) and , respectively, found 12% and 13% adoption in their study areas in agro ecological zones 1 and 2a.…”
Section: Introductionmentioning
confidence: 87%
“…The second category focus on a sub-segment of MT adopters and how CA tillage systems offer maize yield advantages among a sub-segment of MT adopters (Haggblade et al 2011;Haggblade and Tembo 2003;Haggblade et al 2010;Kuntashula, Chabala, and Mulenga 2014;Shitumbanuma 2013;Umar et al 2011Umar et al , 2012. These studies typically use data drawn from case studies of selected areas where CA has been most promoted (Kuntashula 2014), and for one agricultural season. Some of these also focus on MT yield effects, grouping together ripping and planting basins rather than allowing these two fundamentally different tillage methods to have different effects on yields.…”
Section: Introductionmentioning
confidence: 99%
“…Haggblade and Tembo () indicate that maize yields decline by 1–2% for each day delayed in planting after the first possible planting date. CA technology therefore ensures that these losses are reduced to a minimum and contribute to mitigating food and nutrition insecurity in SSA (Kuntashula et al., ).…”
Section: Ca Technology In Zambiamentioning
confidence: 99%
“…In evaluating the impact of a binary variable on a binary outcome like adoption on poverty headcount, other studies have employed Heckman two‐stage selection method to account for observed and unobserved heterogeneity between adopters and nonadopters (e.g., Kuntashula et al., ). This study uses an RBP model to jointly estimate adoption and impact of CA on poverty headcount (Amare et al., ).…”
Section: Empirical Specificationsmentioning
confidence: 99%
“…For example, a countrywide study by Ngoma et al (2013) observed that only about 3.9% among Zambia's population of smallholder farmers practiced MT in 2012. Furthermore, a study by Kuntashula et al (2014) indicated an adoption rate of about 12% from six selected districts in Zambia's agro-ecological region (AER) II in 2012. Zambia has three AERs.…”
Section: Introductionmentioning
confidence: 99%